Meeting the Challenge of Unemployment?. Issue 1 (March 2014) - Nattrass, Nicoli
South Africa has one of the highest rates of unemployment in the world. Job creation is a national priority, yet labor-intensive options are derided by the trade union movement as an unacceptable throwback to the "cheap labor" policies of apartheid, and effectively ruled out by the government in its recent National Development Plan (NDP). Instead, minimum-wage setting in South Africa continues to contribute to job destruction (as evidenced most recently in the clothing industry). Policy-makers hope that support for high-productivity firms and rapid economic growth will make up for job losses and solve the unemployment problem. Unfortunately, South Africa's economic performance has been comparatively disappointing and constrained by negative investor sentiment, especially with regard to the labor market. The NDP has called for a social accord between labor and capital. But the prospects are not promising, and unemployment is likely to remain a significant feature of the South African economic landscape.